A Binational Overview of Reproductive Health Outcomes Among US Hispanic and Mexican Women in the Border Region - Jill A. McDonald, PhD; Octavio Mojarro, MS; Paul D. Sutton, PhD; Stephanie J. Ventura, MA (Centers for Disease Control and Prevention, 2013)
Introduction The US-Mexico border region has 15 million residents and 300,000 births annually. Reproductive health concerns have been identified on both sides of the border, but comparable information about reproductive health is not available. The objective of this study was to compare reproductive health indicators among populations in this region. Methods We used 2009 US Hispanic and Mexican birth certificate data to compare births inside the border region, elsewhere within the border states, and in the United States and Mexico overall. We examined trends in total fertility and birth rates using birth data from 2000 through 2009 and intercensal population estimates. Results Among women in the border region, US women had more lifetime births than Mexican women in 2009 (2.69 births vs 2.15 births) and throughout the decade. Birth rates in the group aged 15 to 19 years were high in both the US (73.8/1,000) and Mexican (86.7/1,000) border regions. Late or no prenatal care was nearly twice as prevalent in the border regions as in the nonborder regions of border states. Low birth weight and preterm and early-term birth were more prevalent in the US border than in the Mexican border region; US border rates were higher and Mexican rates were lower than their corresponding nonborder and national rates. We found some variations within border states. Conclusion These findings constitute the first population-based information on the reproductive health of the entire Hispanic US-Mexico border population. Evidence of disparities warrants exploration at state and local levels. Teen pregnancy and inadequate prenatal care are shared problems in US-Mexico border communities and suggest an area for binational cooperation.